API5 induces cisplatin resistance through FGFR signaling in human cancer cells - Jang, Han Sol (Exp Mol Med, 2017)
Most tumors frequently undergo initial treatment with a chemotherapeutic agent but ultimately develop resistance, which limits the success of chemotherapies. As cisplatin exerts a high therapeutic effect in a variety of cancer types, it is often used in diverse strategies, such as neoadjuvant, adjuvant and combination chemotherapies. However, cisplatin resistance has often manifested regardless of cancer type, and it represents an unmet clinical need. Since we found that API5 expression was positively correlated with chemotherapy resistance in several specimens from patients with cervical cancer, we decided to investigate whether API5 is involved in the development of resistance after chemotherapy and to explore whether targeting API5 or its downstream effectors can reverse chemo-resistance. For this purpose, cisplatin-resistant cells (CaSki P3 CR) were established using three rounds of in vivo selection with cisplatin in a xenografted mouse. In the CaSki P3 CR cells, we observed that API5 acted as a chemo-resistant factor by rendering cancer cells resistant to cisplatin-induced apoptosis. Mechanistic investigations revealed that API5 mediated chemo-resistance by activating FGFR1 signaling, which led to Bim degradation. Importantly, FGFR1 inhibition using either an siRNA or a specific inhibitor disrupted cisplatin resistance in various types of API5(high) cancer cells in an in vitro cell culture system as well as in an in vivo xenograft model. Thus, our results demonstrated that API5 promotes chemo-resistance and that targeting either API5 or its downstream FGFR1 effectors can sensitize chemo-refractory cancers.